Carta de Julián Silva a Roberto H. Todd - Todd, Roberto H.; Silva, Julián (My University, 1905)
Carta relacionada a la Liga de Municipios.
Keywords: Municipal government--Puerto Rico.; Gobierno Municipal--Puerto Rico.